3-month versus 6-month adjuvant chemotherapy for patients with high-risk stage II and III colorectal cancer: 3-year follow-up of the SCOT non-inferiority RCT - Iveson, Timothy; Boyd, Kathleen A; Kerr, Rachel S; Robles-Zurita, José Antonio; Saunders, Mark P; Briggs, Andrew H; Cassidy, Jim; Hollander, Niels Henrik; Tabernero, Josep; Haydon, Andrew; Glimelius, Bengt; Harkin, Andrea; et al. (NIHR JOURNALS LIBRARY, 2019)
Background: Oxaliplatin and fluoropyrimidine chemotherapy administered over 6 months is the standard adjuvant regimen for patients with high-risk stage II or III colorectal cancer. However, the regimen is associated with cumulative toxicity, characterised by chronic and often irreversible neuropathy. Objectives: To assess the efficacy of 3-month versus 6-month adjuvant chemotherapy for colorectal cancer and to compare the toxicity, health-related quality of life and cost-effectiveness of the durations. Design: An international, randomised, open-label, non-inferiority, Phase III, parallel-group trial. Setting: A total of 244 oncology clinics from six countries: UK (England, Scotland, Wales and Northern Ireland), Denmark, Spain, Sweden, Australia and New Zealand. Participants: Adults aged ≥ 18 years who had undergone curative resection for high-risk stage II or III adenocarcinoma of the colon or rectum. Interventions: The adjuvant treatment regimen was either oxaliplatin and 5-fluorouracil or oxaliplatin and capecitabine, randomised to be administered over 3 or 6 months. Main outcome measures: The primary outcome was disease-free survival. Overall survival, adverse events, neuropathy and health-related quality of life were also assessed. The main cost categories were chemotherapy treatment and hospitalisation. Cost-effectiveness was assessed through incremental cost comparisons and quality-adjusted life-year gains between the options and was reported as net monetary benefit using a willingness-to-pay threshold of £30,000 per quality-adjusted life-year per patient. Results: The 3-year disease-free survival rate in the 3-month treatment group was 76.7% (standard error 0.8%) and in the 6-month treatment group was 77.1% (standard error 0.8%), equating to a hazard ratio of 1.006 (95% confidence interval 0.909 to 1.114; p-value for non-inferiority = 0.012), confirming non-inferiority for 3-month adjuvant chemotherapy.
Keywords: Quimioterapia - Ensayos; ADJUVANT; CAPECITABINE; CHEMOTHERAPY; COLORECTAL NEOPLASMS; DISEASE-FREE SURVIVAL; FLUOROURACIL; OXALIPLATIN; QUALITY-ADJUSTED LIFE-YEARS; RANDOMISED CONTROLLED TRIAL